Framing Cardiovascular Health for Rural Populations: Community, Innovation, Evidence-Based Practice, and Technology - Barbara Ann Graves (Rural Nurse Organization; Binghamton University, 2012)
Cardiovascular disease (CVD) is the leading cause of death in the United States. More than twice as many deaths occur due to cardiovascular disease as for all types of cancers combined. Nationally, every year approximately 16 million cases of coronary heart disease are reported (AHRQ, 2005). In 2005 the total cost for all forms of CVD was an astounding $448.5 billion. Furthermore, CVD is associated with many forms of chronic illness which add to the cost and decrease quality of life (AHRQ, 2005). For these reason CVD has received much attention in health research and health policy arenas (Krumholz et al., 2009; Peterson et al., 2007; Yusuf, Reddy, & Anand, 2002). Findings from studies indicate an overall reduction of heart disease risk and mortality in the past three decades (AHA, 2005). While the amount of research noted throughout the literature is overwhelming and heart disease mortality has fallen, heart disease continues to be the single largest killer of men and women in the United States with continuing evidence of variations and disparities that are yet unexplained.